2014
DOI: 10.7567/jjap.53.04ep09
|View full text |Cite
|
Sign up to set email alerts
|

Observation of deep levels and their hole capture behavior in p-type 4H-SiC epilayers with and without electron irradiation

Abstract: This paper reports deep levels in p-type 4H-SiC epilayers with and without electron irradiation by the current deep level transient spectroscopy. We also estimated time constants of hole capture by deep levels and discussed possibility that the deep levels behave as recombination centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Considering the peak temperature and E A , PI1 and PI2 appear to be similar to those observed in electron-irradiated Al-doped p-type 4H-SiC. [19] PI3 corresponds to the Z 1/2 center, whereas PI4 and PI5 correspond to the RD 1/2 and EH 6/7 centers, respectively. [20,[29][30][31][32] The parameters for the deep levels and the speculated corresponding centers are summarized in Table 2.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…Considering the peak temperature and E A , PI1 and PI2 appear to be similar to those observed in electron-irradiated Al-doped p-type 4H-SiC. [19] PI3 corresponds to the Z 1/2 center, whereas PI4 and PI5 correspond to the RD 1/2 and EH 6/7 centers, respectively. [20,[29][30][31][32] The parameters for the deep levels and the speculated corresponding centers are summarized in Table 2.…”
Section: Resultssupporting
confidence: 67%
“…In addition, it has been reported that the negative peak signals in the n‐type semiconductor, such as PI1 and PI2, originate from the hole‐like traps, [ 33,34 ] and E A of PI1 and PI2 are similar to the deep levels observed by DLTS for p‐type SiC. [ 19 ] Therefore, we consider that these peaks originate from the hole traps in the n‐type layer, and minority carriers might be injected to the hole traps by reverse currents during the filling pulse with ≈10 −9 A cm −2 . In addition, considering the correspondence with the reported 17A‐1 and e17‐1 centers, [ 18 ] PI1 and PI2 will originate from intrinsic or complex Al‐related defects.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations